POLA AKTIVITAS REMAJA PECANDU VIDEO PORNO (Studi Kasus: Remaja di Nagari Pamuatan Kecamatan Kupitan Kabupaten Sijunjunjung). - YENI, LARA NOFITRI (Pendidikan Sosiologi, 2014)
Throughout 2014 there were 10 adolescents aged 17 to 19 years ranges pregnantoutside marriage in Nagari Pamuatan. Case his pregnant the teenagers outside marriage,because teenagers like to watch porn videos. And as well as watch their favorite pornvideos encouraging them to practice scenes in the videos they watch the real world, as forthe problems in this study a) What is the pattern of activity in the porn video teen addictsNagari Pamuatan,subdistan Kupitan, Sijunjung district b) What is the impact of addictionto watch video porn of teens in Nagari Pamuatan.The theory used in this study is the social exchange theory described by GeorgeHomans. Social exchange theory see between the behavior of the environment there is arelationship of mutual influence (reciprocal). This research is qualitative with descriptivemethod. The method of data collection was through deep interviews and observation. Keyinformant interviews were conducted with as many as 8 people, informants in this studywere taken by using a snowball sampling technique. Model analysis of the data is throughthe stages of data collection, data reduction, data presentation and conclusion.The results showed that the pattern of activity in the porn video teen addictsNagari Pamuatan, sub District of Kupitan Sijunjung distprict famend: (1) a teenager whoused to watch in internet cafes and at home, (2) the average time to watch at the internetcafe between 5-6 hours with untensitas 5-7 times a week, (3) has a collection of pornvideos (4) attitude when watching in internet cafes is individualism and do not want to bedisturbed, and attitude are watching at home masturbation, (5) has a porn video websitesthat are often open (6) the total cost incurred perminggunya is at least Rp. 100,000.